2020
DOI: 10.1364/ao.383232
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of keyhole entrance and molten pool with quality analysis during adjustable ring mode laser welding

Abstract: The process monitoring of the top side and the evaluation of surface quality were applied in adjustable ring mode (ARM) laser welding of 316 stainless steel by using visual monitoring and confocal sensor technology. Experiments were conducted in different power arrangements of an ARM laser. In this study, the process status was evaluated based on the area of keyhole entrance and the width of the pool. The geometric characteristics of the topside weld were measured by a confocal sensor. The shape of the fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The inner core promotes the generation of the keyhole, while the ring-shaped laser beam allows controlling the distribution of temperature and cooling rate in and around the molten pool. Research has confirmed a positive effect of ARM laser on keyhole stabilization [15]. The stability of the keyhole and, therefore, of the welding process is a vital indicator of the weld quality in those applications where partial penetration is required, such as welding of battery tab connectors.…”
Section: Introductionmentioning
confidence: 93%
“…The inner core promotes the generation of the keyhole, while the ring-shaped laser beam allows controlling the distribution of temperature and cooling rate in and around the molten pool. Research has confirmed a positive effect of ARM laser on keyhole stabilization [15]. The stability of the keyhole and, therefore, of the welding process is a vital indicator of the weld quality in those applications where partial penetration is required, such as welding of battery tab connectors.…”
Section: Introductionmentioning
confidence: 93%
“…The separator, which was heated to more than 160ºC, shrank horizontally, causing a short circuit due to direct contact of the cathode material and anode material. 4) Continued laser irradiation produced a molten pool (9) . The molten pool contributed to stable heating of these areas, expanding the short circuit area.…”
Section: Estimated Process Of Thermal Runaway Caused By Lasermentioning
confidence: 99%
“…In addition to ordinary monitoring sensors, some special technologies can be used, such as on-line coherent imaging [60], X-ray diffractometer [61] and Hanover analyzer [62]. From the current research, the detection of laser welding process signal mainly focuses on sound, light, electricity and heat [63][64][65][66][67][68][69][70][71].…”
Section: Single Signal Monitoringmentioning
confidence: 99%